Remaining Service Life Discharge Conveyor G pada Tambang Batubara PT GHI di Kabupaten Tanah Laut, Provinsi Kalimantan Selatan - Nurul Azizah; Elfida Moralista; Zaenal (Bandung Conference Series: Mining Engineering, 2023)
Abstract. The transfer of coal material at PT GHI in Tanah Laut Regency, South Kalimantan Province usually uses conveyors. This conveyor is one of the mechanical devices used to move material from one place to another. This conveyor structure has a carbon steel base material which is a material that is prone to corrosion. This corrosion is caused by a reaction with the surrounding environment and the presence of impurities in coal. For this reason, it is necessary to monitor and control corrosion. This study aims to determine the type of corrosion that occurs, corrosion control methods, and the corrosion rate and remaining service life of the conveyor structure.The research was conducted on a 94 meter long conveyor structure which was divided into 3 segments consisting of 25 test points. The methodology in this research is thickness reduction measurement. Measurements were made on the conveyor structure using the Smart Sensor Ultrasonic Thickness Gauge TT 130. Data on nominal thickness, actual thickness and service life are used to calculate the corrosion rate and remaining service life of the conveyor structure. Environmental conditions in the research area based on data from 2015 - 2019 have an average rainfall of 229.26 mm / year, an average relative humidity of 79.44% and an average temperature of 28.16ºC.The type of corrosion that occurs on the conveyor structure is uniform corrosion. The corrosion control method used is the Three Layers System Coating method with primary coating using Seaguard 5000, intermediate coating using Sherglass FF, and top coating using Aliphatic Acrylic Modified Polyurethane Abstrak. Pemindahan material batubara di PT GHI di Kabupaten Tanah Laut, Provinsi Kalimantan Selatan ini biasanya menggunakan Conveyor. Conveyor ini merupakan salah satu alat mekanis yang digunakan untuk memindahkan material dari satu tempat ke tempat lainnya. Struktur Conveyor ini memiliki bahan dasar baja karbon yang mana material ini merupakan material yang rawan terhadap korosi. Korosi ini disebabkan adanya reaksi dengan lingkungan sekitar dan adanya pengotor pada batubara. Untuk itu perlu dilakukan monitoring dan pengendalian korosi. Penelitian ini bertujuan untuk mengetahui jenis korosi yang terjadi, metode pengendalian korosi, dan laju korosi dan sisa umur pakai struktur conveyor. Penelitian dilakukan pada struktur Conveyor sepanjang 94 meter yang terbagi menjadi 3 segmen yang terdiri dari 25 test point. Metodologi dalam penelitian ini adalah pengukuran pengurangan ketebalan. Pengukuran dilakukan pada struktur conveyor menggunakan alat Smart Sensor Ultrasonic Thickness Gauge TT 130. Data tebal nominal, tebal aktual dan umur pakai yang digunakan untuk menghitung corrosion rate serta remaining service Life dari struktur conveyor. Kondisi lingkungan di daerah penelitian berdasarkan data dari tahun 2015 – 2019 memiliki curah hujan rata-rata 229,26 mm/tahun, kelembapan relatif rata-rata 79,44% dan temperatur rata-rata 28,16ºC. Jenis korosi yang terjadi pada struktur conveyor merupakan korosi merata. Metode pengendalian korosi yang digunakan merupakan metode Coating Three Layers System dengan primer coating menggunakan Seaguard 5000, intermediate coating menggunakan Sherglass FF, dan top coating menggunakan Aliphatic Acrylic Modified Polyurethane